The Potency of Anadara nodifera Shell as Natural Testosterone Booster for Male Canary (Seriunus canaria) - Pudji Astuti; Muhammad Naufal Prayitno Putra; Muhammad Fariz Ash Shiddiq; Rizki Fitrawan Yuneldi; Claude Mona Airin; Sarmin Sarmin (Bogor Agricultural University, Indonesia, 2022)
Anadara clam shell contains high Zinc. This microelement is recognised as acting natural aromatase blocker (NAB) that capable of boosting testosterone level. The aim of this study was to evaluates the testosterone level of Canaries following Anadara nodifera administration. Adult male Canaries (n = 27) were group into 3 with 9 repetition of each i.e T0 [control, was given by Carboxymethyl Cellulose Sodium (Na-CMC)], T1 (Zinc Sulphate 0.013 mg/30 g BW), and T2 (NAB 0.3 mg/30 g BW). The T2 treatment was NAB or shell powder of Anadara nodifera which was diluted 1:1 in Na-CMC. The birds were treated orally for 21 days. The complete blood cell count was performed in a haemo analyser except the erythrocyte was calculated manually in the Improved Neubauer counting chamber. Testosterone level was measured in ELISA. Subsequently gen CYP19 aromatase in syrinx, brain and testis were identified employing IHC and descriptively analysed. The result indicated significant elevated level of testosterone (p<0.05). The expression of CYP19 aromatase receptor was depressed in syrinx, brain and testis. However there was no significant changes on the blood profile (p>0.05). To conclude, Anadara nodifera at 0.3 mg/30 g BW was capable of acting as NAB to promote testosterone level. This was confirmed by the reduction of CYP19 aromatase gene receptors in syrinx, brain and testis. However NAB treatment was not significantly affecting routine blood profile.